The Multiple Mediation Impact of Adolescents Physical Fitness and Cognitive Perceptions on Their Objective Measures – the Cogni-Action Project - De Moraes-Ferrari, G (Elsevier Ltd, 2024)
Objective: To establish whether physical fitness and cognitive self-perceptions act as mediators in the link between global fitness and cognitive performance measured objectively in adolescents. We also compared differences across sex. Methods: A total of 1296 adolescents (50 % girls) from grades 5 to 8 (ages 10–14) participated in this cross-sectional study. The ALPHA-fitness test battery assessed physical fitness, comprising cardiorespiratory, speed-agility, and muscular fitness components. We used the 1–5-point International Fitness Scale for physical fitness self-perception, and the 1–10 scale for cognitive performance self-perception. Objective cognitive performance was assessed using a neurocognitive battery consisting of eight tasks. Using principal component analysis, these tasks were grouped into three domains: attention, working memory, and problem solving. We examined three serial mediation models adjusted for sex, standardized body mass index, maturation, and school vulnerability index. Results: Physical fitness and cognitive self-perceptions mediated the effects on attention (B = .0027, CI = .0011 to .0047), memory (B = .0025; CI = .0003 to .0055 and B = .0035; CI = .0009 to .0063), and problem-solving (B = −.0137; CI = −.0231 to −.0052 and B = .0072; CI = .0043 to .0106). By sex, boys showed mediation in all domains, while girls only showed mediation in problem-solving. Conclusions: Adolescents perceptions play a crucial and positive mediating role in linking objective measures of physical fitness to cognitive performance outcomes, particularly when self-perceptions of physical fitness and cognition are considered together. Therefore, educating families and school/health environments about the importance of adolescent perceptions, while fostering self-awareness and reinforcing their capabilities, is essential. © 2024